Efficacy of an internet-based self-help intervention to reduce co-occurring alcohol misuse and depression symptoms in adults: study protocol of a three-arm randomised controlled trial. Issue 5 (25th May 2016) - Schaub, Michael P; Blankers, Matthijs; Lehr, Dirk; Boss, Leif; Riper, Heleen; Dekker, Jack; Goudriaan, Anna E; Maier, Larissa J; Haug, Severin; Amann, Manuel; Dey, Michelle; Wenger, Andreas; et al.
Abstract : Introduction: In the general population, alcohol use disorder and depression more often occur together than any other combination of a mental illness with a substance use disorder. It is important to have a cost-effective intervention that is able to reach at-risk individuals in the early stages of developing alcohol use disorders and depression disorders. Methods and analysis: This paper presents the protocol for a 3-arm multicentre randomised controlled trial (RCT) to test the efficacy and cost-effectiveness of the combined internet-based self-help intervention Take Care of You (TCOY) to reduce alcohol misuse and depression symptoms in comparison with a waiting list control group and a comparable intervention focusing on problematic alcohol use only. The active interventions consist of modules designed to reduce alcohol use, based on the principles of motivational interviewing and methods of cognitive behavioural therapy, together with additional modules in the combined study arm to reduce symptoms of depression. Data will be collected at baseline, as well as at 3 and 6 months postrandomisation. The primary outcome is the quantity of alcohol used in the past 7 days. A number of secondary outcome measures will be studied. These include the Centre of Epidemiologic Studies of Depression Scale (CES-D) and a combined measure with the criteria of values below the cut-off for severe alcohol use disorder and for CES-D. Data analysis will follow the intention-to-treat principle using (generalised) linear mixed models. In order to investigate the interventions' cost-utility and cost-effectiveness, a full economic evaluation will be performed. Ethics and dissemination: This RCT will be executed in compliance with the Helsinki Declaration and has been approved by 2 local Ethics Committees. Results will be reported at conferences and in peer-reviewed publications. Participant-friendly summaries of trial findings will be published on the TCOY websites. Trial registration number: ISRCTN10323951.